2013
DOI: 10.3766/jaaa.24.8.6
|View full text |Cite
|
Sign up to set email alerts
|

The Advantage of Knowing the Talker

Abstract: Background Many audiologists have observed a situation where a patient appears to understand something spoken by his/her spouse or a close friend but not the same information spoken by a stranger. However, it is not clear whether this observation reflects choice of communication strategy or a true benefit derived from the talker’s voice. Purpose The current study measured the benefits of long-term talker familiarity for older individuals with hearing impairment in a variety of listening situations. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 53 publications
8
66
4
Order By: Relevance
“…Furthermore, these data showed that a person's familiarity with the talker did not influence the size of the ISE, whether the participants were informed of the talker's identity (Experiment 1) or received four days of talker training that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 required them to attend to and interact with talker-specific characteristics of the voice (Experiment 2). These findings are in contrast to our hypotheses and previous speech perception research comparing listeners' perception of words spoken by familiar and unfamiliar voicesfamiliarity with the talker's voice typically yields a perceptual advantage (e.g., Barker & Newman, 2004;Souza et al, 2013;Yonan & Summers, 2000). However, it is important to note, the majority of these aforementioned studies exploring talker familiarity utilized talkers that the listeners had long-standing, personal relationships with (e.g., a parent or spouse).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, these data showed that a person's familiarity with the talker did not influence the size of the ISE, whether the participants were informed of the talker's identity (Experiment 1) or received four days of talker training that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 required them to attend to and interact with talker-specific characteristics of the voice (Experiment 2). These findings are in contrast to our hypotheses and previous speech perception research comparing listeners' perception of words spoken by familiar and unfamiliar voicesfamiliarity with the talker's voice typically yields a perceptual advantage (e.g., Barker & Newman, 2004;Souza et al, 2013;Yonan & Summers, 2000). However, it is important to note, the majority of these aforementioned studies exploring talker familiarity utilized talkers that the listeners had long-standing, personal relationships with (e.g., a parent or spouse).…”
Section: Discussioncontrasting
confidence: 99%
“…Performance on the local Midland talkers was consistently at 97% accuracy throughout experiment 1, but performance on the non-local Northern talkers ranged from 83 to 96% accuracy across experiments, and performance on the non-local Southern talkers ranged from 80 to 93% accuracy in experiment 2. These results are consistent with previous research suggesting that familiarity with a specific dialect can facilitate speech processing (Clopper, 2014;Floccia et al, 2006;Sumner and Samuel, 2009; see also Nygaard and Pisoni, 1998;Souza et al, 2013, on comparable talker familiarity effects).…”
Section: Familiarity Localness and Enregistermentsupporting
confidence: 82%
“…Naturalistic speech-in-noise situations offer multiple cues, many of them redundant, that can result in flexibility in how the task is solved. This is true to a lesser degree of clinical tests of SIN (including the HINT variant used here), which approximate the naturalistic experience of perceiving speech masked by sound, but lack factors that are important in real-life conversations such as familiarity with the talker [Nygaard et al, 1994; Souza et al, 2013], visual cues [Zion Golumbic et al, 2013], and context- and listener-dependent adaptations of the speaker [Lombard, 1911]. Tasks that have been used to study the neural correlates of SIN perception range in cue-richness from natural language comprehension in daily life, to intermediate tasks like the sentence-in-noise and word-in-noise measures, to discrimination of phonemes from among a restricted set of possibilities [Du et al, 2014], and finally to passively listening to single sounds with or without masking noise.…”
Section: Discussionmentioning
confidence: 99%